Barter scheme in supply chain of traditional wet market during COVID-19 pandemic. (4th November 2022) - Sutanto, Sutanto; Wiwoho, Jamal; Aini, Intan Novela Qurrotul; Christy, Alexander Yonathan
Since early 2020, coronavirus disease 2019 (COVID-19) has become a global pandemic. This disease spreads through person-to-person by physical contact, thus physical distancing is effective to prevent the virus transmission. The retailers in the traditional wet market cannot adapt to this policy due to the lack of internet literature while most of the customers change to online shopping habits. Furthermore, the decreasing number of transactions in the market may lead to bigger problems such as expiring products, prices fluctuation, and inflation. This research formulates a supply chain model with a barter scheme and third party to connect the retailer and online customers. The barter scheme allows retailers to exchange their products with other products for living and reduce the risk of loss caused by expired products, while the third party promotes online sales and manages the barter in the system.